Doppler Effect Moving source, stationary observer:
Doppler Effect Moving source, stationary observer:
Doppler Effect Moving source, stationary observer:
Doppler Effect Moving source, stationary observer:
Doppler Effect Moving source, stationary observer:
Doppler Effect Moving source, stationary observer: Wavelength here Is increased
Doppler Effect Moving source, stationary observer: Wavelength here Is decreased Wavelength here Is increased
Doppler Effect Moving source, stationary observer: This is where the car WAS when the first wave-front was emitted
Doppler Effect Moving source, stationary observer: This is where the car was when the SECOND wave-front was emitted
Doppler Effect Moving source, stationary observer: If the emitted wave has frequency, f then the time between Wave-fronts Is simply the PERIOD, T = 1f1f
Doppler Effect Moving source, stationary observer: If the emitted wave has frequency, f then the time between Wave-fronts Is simply the PERIOD, T = The car has moved a distance of v s x T, or 1f1f vs fvs f
Doppler Effect Moving source, stationary observer: If the emitted wave has frequency, f then the time between Wave-fronts Is simply the PERIOD, T = The car has moved a distance of v s x T, or 1f1f So the wavelength here is INCREASED by vs fvs f vs fvs f
Doppler Effect Moving source, stationary observer: If the emitted wave has frequency, f then the time between Wave-fronts Is simply the PERIOD, T = The car has moved a distance of v s x T, or 1f1f So the wavelength here is INCREASED by And the wavelength here is DECREASED by vs fvs f vs fvs f vs fvs f
Source Moving Towards Us: Wavelength decreases by Δλ = vsfvsf
Source Moving Towards Us: Wavelength decreases by Δλ = So λ moving = λ stationary – Δλ vsfvsf
Source Moving Towards Us: Wavelength decreases by Δλ = So λ moving = λ stationary – Δλ But since v = f λ, we can substitute for λ (= ) vsfvsf vfvf
Source Moving Towards Us: Wavelength decreases by Δλ = So λ moving = λ stationary – Δλ But since v = f λ, we can substitute for λ (= ) v = v - v s vsfvsf vfvf f moving f stationary f stationary
Source Moving Towards Us: Wavelength decreases by Δλ = So λ moving = λ stationary – Δλ But since v = f λ, we can subtitute for λ (= ) v = v - v s vsfvsf vfvf f moving f stationary f stationary v v - v s () f’ = f
Doppler Effect and the BIG BANG How does a star’s motion affect the light? What does a ‘red shift’ mean? If hydrogen emits light at a fixed frequency, how can we determine whether a star is moving? How old is the universe? How do we know this? What other evidence is there for the Big Bang model? How can powerful telescopes tell us what happened billions of years ago?